Implementation Of FlashCard Learning Media For Student Learning Motivation And Arabic Language Subject (At MI Miftahul Ulum 01 Cukur Guling Kulon 1 Lumbang Pasuruan East Java) - Hurroh, Qoidatul; Ma'ruf, Ahmad; Abdullah , Muhammad (Jurnal Pendidikan Indonesia, 2023)
The problem in learning Arabic today is that the level of enthusiasm of students is still limited when Arabic teaching activities take place. Lack of response to what has been taught by the teacher, especially the vocabulary that has been given. Low motivation in participating in Arabic learning, Lack of understanding that students are responsible for themselves. The focus of this research is to find out the Implementation of Flashcard Learning Media to Motivate Students to Learn Arabic and, Knowing the Strengths and Weaknesses of Implementation of Flashcard Learning Media to Motivate Students to Learn Arabic At Mi Miftahul Ulum 01 shaving roll kulon 1 Lumbang Pasuruan. . The use of this media gives rise to many positive things such as students will be more familiar with various kinds of questions related to various elementary level materials, train their memory, and learning outcomes will increase. And by using this learning media students will always be encouraged and motivated to learn, learn, and learn more. And student learning motivation increases and can affect the institution. this is from the students themselves and the teacher's strategy which is less effective in attracting the interest of each student to use this Arabic flashcard learning media. The second is Knowing the Strengths and Weaknesses of Implementation of Flashcard learning media for student motivation in Arabic subjects at MI Miftahul Ulum 01. While the advantages, the advantages in using flashcard learning media are the principal, all teacher boards, especially Arabic teachers because they are young and can it's easy to make yourself. In addition, student guardians are very enthusiastic and supportive in using this flashcard learning media. And the drawbacks are Only visual media, Image size is often inappropriate for teaching in large groups, Requires the availability of resources and skills, and the teacher's foresight to be able to use it.